Film as A Media Used by Teachers to Teach Writing for Tertiary Level Students - Ardayati Ardayati (Linguistic, English Education and Art (LEEA) Journal, 2018)
The aim of this research was to find out whether or not it was significantly effective to use film as a media in teaching writing for tertiary level students. This study used preexperimental method which was focused on writing skill at the eleventh grade students of Senior High School Tugumulyo. The writer formulated two hypotheses; they were null hypothesis (Ho) and the alternative hypothesis (Ha). There were 352 students from nine classes as the population of this study. The sample was taken through cluster random sampling. The result was XI IA.2 class which consisted of 37 students. In this case, the writer collected the data by using writing test. Based on the findings, the result showed that tobtained was 6.38 where ttable was 1.697. It showed that tobtained was higher than ttable (tobtained more than ttable). Finally, the writer concludes that it was significantly effective to use film as media in teaching writing at the eleventh grade students of Senior High School Tugumulyo. Keywords: teaching writing, film, media.